2017
DOI: 10.22616/rrd.23.2017.040
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance of aeromonas spp. isolated from the sea trout (Salmo trutta L.) in Latvia

Abstract: The aim of this study was to investigate the patterns of antibiotic resistance of Aeromonas spp. bacteria isolated from the sea trout (Salmo trutta) from the state fish hatcheries of the Institute of Food Safety, Animal Health and Environment 'BIOR', Latvia. Bacteriological investigations were performed at four state fish hatcheries located in the drainage basins of the main Latvian rivers -Daugava, Venta and Gauja, during the five-year period (2012 -2016). In fish with visible clinical signs, bacteriological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
(16 reference statements)
1
3
1
Order By: Relevance
“…Interestingly, these researchers also observed a resistance to gentamicin and amikacin of 17.19% and 12.50%, respectively [ 31 ]. In contrast to our results, Hossain et al [ 6 ], Revina et al [ 13 ], John et al [ 24 ], Stratev et al [ 22 ], Dood N. [ 26 ], Vivekanandhan et al [ 29 ], and Odeyemi et al [ 35 ] reported that the least resistance was to aminoglycosides.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Interestingly, these researchers also observed a resistance to gentamicin and amikacin of 17.19% and 12.50%, respectively [ 31 ]. In contrast to our results, Hossain et al [ 6 ], Revina et al [ 13 ], John et al [ 24 ], Stratev et al [ 22 ], Dood N. [ 26 ], Vivekanandhan et al [ 29 ], and Odeyemi et al [ 35 ] reported that the least resistance was to aminoglycosides.…”
Section: Discussioncontrasting
confidence: 99%
“…Resistant Aeromonas spp. have been identified in various aquatic sources, including sea trout in Latvia; ornamental fish in India; goldfish in Korea and Thailand (100% amoxicillin resistance); diseased ornamental fish in Thailand (92.31% were resistant to penicillin and amoxicillin, and 83.33% were resistant to ampicillin); skin and water from imported ornamental fish in Portugal (95% were resistant to amoxicillin, 96% resistant to carbenicillin, and 94% resistant to ampicillin); fish and prawn in south India (100% were resistant to methicillin); and water and fish from freshwater fish farms in Syria (more than 75% were resistant to amoxicillin) [ 6 , 13 , 23 , 24 , 26 , 29 , 30 , 31 ]. Beta-lactam tolerance in bacteria is frequently due to the presence of the beta-lactamase enzyme, which is produced by aeromonads and many strains of Gram-negative bacilli.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These changes may be due to differences in geographical distribution or treatment regimes. The in-vitro susceptibility tests for the isolated A. hydrophila showed that the tested A. hydrophila strains were highly resistant to amoxicillin may suggest the production of beta-lactamase, which is constant with the findings of Daood, (2012) and Revina et al, (2017). The results of PCR for amplification of blaTEM gene in V. parahaemolyticus strains showed that the blaTEM gene was amplified in all 5 V. Ibrahim (2015) and Okolie (2015).…”
Section: Discussionsupporting
confidence: 60%